A relação entre crescimento econômico e desenvolvimento sustentável: a Região do Araguaia no contexto regional paraense - SILVA, Luciene de Jesus Maciel da (Universidade Federal do Pará, 2012)
The relationship between economic growth and sustainable development is the issue that this study proposes to examine this by using the Index of Sustainable Local Development- IDLS. In this sense, the category of analysis used was the region which is defined as a system formed by and from the combination of internal and external elements. The object of analysis selected was the Araguaia region of Para which is located in the State of Pará - Brazil, this choice was because, over the past 40 years, this region has made significant economic role in this state and at the same time, has been the focus of questions about the economic development model used in the past and the present results. The main objective of this study is to analyze, through internal and external elements of a region regarded as frontier resources, if the scenario of economic growth has contributed to sustainable development. The selection of a case study was the research strategy and data collection instruments were: the use of questionnaires, analysis of the evolution of secondary data and the construction of a Sustainable Local Development Index (IDS) that was used to scale the integrated manner the social, environmental, economic and institutional area surveyed in relation to the regional context of Pará. The main result of this study was the observation that economic growth in the regions of Pará to the present procedures did not mediate the favorable development towards sustainability. It was observed that the Araguaia region, is on alert in IDLs, following the same trend in other regional areas that have grown economically in the state of Pará. For each region of the state of Para, a different dimension committed to regional sustainability. In the case of the Araguaia region of the environmental dimension was the most compromised your IDSL. This result proves that several studies have claimed that the environmental impacts jeopardize the sustainable development of the region. Nevertheless, this region had the third best performance in the social dimension of sustainability as more important for sustainable development that this study was to measure. Therefore, two main conclusions can be pointed out. The first is that currently there was an improvement in the social pattern of the regions of Pará as a whole, in some cases the central areas of major social investments outperformed other regions that did not focus on investment promotion in previous decades. Although some studies suggest that government investment is not coated in social benefits. The second is that the elements external to the regions contributed to the change of membership described, but not to change the regional environmental framework, because it created institutionalities conduct internal forces in the production of the results of the economic framework, social, institutional and environmental. Therefore, both the elevation of social status and worsening the region's environmental Araguaia Para are the result of a set of national policies that probably were added to the scenarios of action and decision of local actors.